The Function and Role of the Cilium in the Development of Ciliopathies - Mancuso, Alessio; Ceravolo, Ida; Cuppari, Caterina; Sallemi, Alessia; Fusco, Monica; Ceravolo, Antonio; Farello, Giovanni; Iapadre, Giulia; Zagaroli, Luca; Nanni, Giuliana; Conti, Giovanni (Journal of Pediatric Neurology, 2022)
“Ciliopathies” are a group of genetic disorders described by the malformation or dysfunction of cilia. The disorders of ciliary proteins lead to a range of phenotype from organ-specific (e.g., cystic disease of the kidney, liver, and pancreas, neural tube defects, postaxial polydactyly, situs inversus, and retinal degeneration) to sketchily pleiotropic (e.g., Bardet-Biedl syndrome and Joubert syndrome). The mechanism below the disfunction of cilia to reach new therapeutic strategies.
Keywords: cilium; ciliopathies; Joubert syndrome